Ejection of ferrofluid grains using nonlinear acoustic impulses— A particle dynamical study - Sen, Surajit; Manciu, Marian; Manciu, Felicia S. (Applied physics letters, 1999)
We consider a model dilute ferrofluid with the grains suspended in water (e.g.,γ-Fe2O3) and subject the system to a strong, homogeneous magnetic field directed perpendicular to the surface such that there is chain formation along the field direction. We show that an appropriate impulse initiated at the base of the container might travel as a nondispersive soliton pulse with sufficient energy to overcome surface tension and eject the ferrofluid grain nearest to the liquid–air interface. The proposed mechanism, if successfully realized in the laboratory, could help design a nozzle-free, ink-jet printer of unparalleled resolution.